Iatrogenic vesicovaginal fistula repair-experience at Prince Hussein Urology and Organ Transplant Center - Al-Hammouri, Firas; Alkaabneh, Awad B.; Abu Qamar, Adnan A.; Naemat, Abdelhakeem S.; Almajali, Ashraf S.; Zraigat, Ali S.; Abdeldaem, Muhammed A. (International Journal of Research in Medical Sciences, 2019)
Background: Despite the advances in technology in urology practice, and the surgical approach in dealing with iatrogenic vesicovaginal fistula repair, the most important is to achieve continent rate with minimum morbidity. Methods: From January 2006 to December 2017, the medical records and operative notes of 52 female (mean age 37 year) who had undergone transabdominal transvesical operative repair of their vesicovaginal fistula (VVF) at this institution were reviewed retrospectively. CT urography and diagnostic cystourethroscopy were the modalities of diagnostic tools. Trans-abdominal, transvesical repair with omental flap interposition were performed within 4-6 months in all cases. Patients were evaluated at two to three weeks initially, then at three months interval and later annually. Results: In present study, the most common presentation of VVF was urine leakage through vagina. In two third of the patients the etiology was due to hysterectomy procedure, regarding the location of the fistula, 94.2% of the fistulas located high in the posterior wall of the urinary bladder (supratrigonal), with the mean size of 2.2cm (range 5-25mm). 49 patients had single fistula (94.2%). The mean operative time was 110 minutes (range 60-130 minutes) and the mean post-operative urethral catheterization was 21 days (range 17-24 days). Almost all patients were continent after a mean of five months. Conclusions: Iatrogenic VVF is one of the distressing complications of gynecological procedure; delayed transabdominal transvesical approach with omental flap interposition is associated with excellent and durable results with minor morbidity. Standardization of the technique is a key success in the outcome of the repair.